Improved CAR internalization and recycling through transmembrane domain optimization reduces CAR-T cytokine release and exhaustion - Xie, Shufeng; Long, Jinlan; Wang, Ruiheng; Xiang, Rufang; Xian, Huajian; Wang, Yixin; Dou, Weiyu; Zhang, Wenjie; Li, Dan; Kang, Ting; Chen, Zhihong; Zhao, Chunjun; et al. (Frontiers in Immunology, 2025)
BackgroundAnti-CD19 chimeric antigen receptor T (CAR-T) cell therapy has proven effective for treating relapsed or refractory acute B cell leukemia. However, challenges such as cytokine release syndrome, T cell dysfunction, and exhaustion persist. Enhancing CAR-T cell efficacy through changing CAR internalization and recycling is a promising approach. The transmembrane domain is the easiest motif to optimize for modulating CAR internalization and recycling without introducing additional domains, and its impact on CAR internalization and recycling has not yet been thoroughly explored. In this study, we aim to enhance CAR-T cell function by focusing on the solely transmembrane domain design.MethodsUtilizing plasmid construction and lentivirus generation, we get two different transmembrane CAR-T cells [19CAR-T(1a) and 19CAR-T(8α)]. Through co-culture with tumor cells, we evaluate CAR dynamic change, activation levels, exhaustion markers, mitochondrial function, and differentiation in both CAR-T cells. Furthermore, immunofluorescence microscopy analysis is performed to reveal the localization of internalized CAR molecules. RNA sequencing is used to detect the transcriptome of activated CAR-T cells. Finally, a mouse study is utilized to verify the anti-tumor efficacy of 19CAR-T(1a) cells in vivo.ResultsOur findings demonstrate that 19CAR-T(1a) has lower surface CAR expression, faster internalization, and a higher recycling rate compared to 19CAR-T(8α). Internalized 19CAR(1a) co-localizes more with early and recycling endosomes, and less with lysosomes than 19CAR(8α). These features result in lower activation levels, less cytokine release, and reduced exhaustion markers in 19CAR-T(1a). Furthermore, CAR-T cells with CD1a transmembrane domain also exhibit a superior anti-tumor ability and reduced exhaustion in vivo.ConclusionOverall, we demonstrate that the transmembrane domain plays a critical role in CAR-T cell function. An optimized transmembrane domain can alleviate cytokine release syndrome and reduce CAR-T cell exhaustion, providing a direction for CAR design to enhance CAR-T cell function.